Evaluasi Sinergitas Program CSR Bank BCA Ponorogo dalam Mendukung Kebijakan Pemerintah Daerah untuk Percepatan Penurunan Angka Stunting - Erysa Nimastuti; Sri Roekminiati; Ika Devy Pramudiana; Sapto Pramono (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
The acceleration of stunting reduction in Ponorogo Regency faces challenges regarding the complexity of the issue and regional fiscal constraints, necessitating strategic cross-sectoral collaboration. This study aims to evaluate the synergy of Bank BCA's Corporate Social Responsibility (CSR) program through the "Bakti BCA" scheme in supporting local government policies related to specific and sensitive nutrition interventions. This research employs a qualitative approach with a case study design. Data collection was conducted through in-depth interviews with key informants from Bank BCA Ponorogo management, Bappeda, the Health Office, and beneficiary families, complemented by participatory observation and a review of the Regional Action Plan (RAD) documents. Data analysis was performed interactively by integrating the Collaborative Governance framework from Ansell and Gash, William N. Dunn's six policy evaluation criteria, and Mark Moore's Public Value concept to analyze the dynamics of cooperation and program performance achievements. The results indicate that the established synergy meets the criteria of appropriateness and effectiveness, where CSR interventions successfully bridged the gap in sanitation services and nutritional fulfillment in stunting locus villages uncovered by the regional budget (APBD). This collaboration proved successful in creating public value in the form of improved physical health status of toddlers, regional budget efficiency, and high community responsiveness. It can be concluded that this strategic partnership effectively accelerates the achievement of stunting reduction targets through equitable resource distribution. This study recommends that private sector engagement be formally integrated from the development planning deliberation (Musrenbang) stage to ensure long-term impact sustainability.